Autophagy Links Inflammasomes to Atherosclerotic Progression - Razani, Babak (2012)
We investigated the role of autophagy in atherosclerosis. During plaque formation in mice, autophagic markers co-localized predominantly with macrophages (mϕ). Atherosclerotic aortas had elevated levels of p62, suggesting that dysfunctional autophagy is characteristic of plaques. To determine if autophagy directly influences atherogenesis, we characterized Beclin-1 heterozygous-null and mϕ-specific ATG5-null (ATG5-mϕKO) mice, commonly used models of autophagy haploinsufficiency and deficiency, respectively. Haploinsufficent Beclin-1 mice had no atherosclerotic phenotype, but ATG5-mϕKO mice had increased plaques suggesting an essential role for basal levels of autophagy in atheroprotection. Defective autophagy is associated with pro-atherogenic inflammasome activation. Classic inflammasome markers were robustly induced in ATG5-null mϕ, especially when co-incubated with cholesterol crystals. Moreover, cholesterol crystals appear to be increased in ATG5-mϕKO plaques, suggesting a potentially vicious cycle of crystal formation and inflammasome activation in autophagy-deficient plaques. These results show that autophagy becomes dysfunctional in atherosclerosis and its deficiency promotes atherosclerosis in part through inflammasome hyperactivation.